Bangladesh Tertiary Education Sector Review : Skills and Innovation for Growth - Rahman, Tashmina; Nakata, Shiro; Nagashima, Yoko; Rahman, Mokhlesur; Sharma, Uttam; Rahman, Muhammad Asahabur (World Bank, Washington, DC, 2019)
Bangladesh is recognized globally for its remarkable track record of socioeconomic development and potential for becoming an economic powerhouse in the region. The economy has sustained impressive economic growth over the past three decades despite incidences of political conflict, natural calamities, and financial shocks. The country met the Millennium Development Goals ahead of time and reduced the poverty level substantially over the past decades. Progress in human development, education, and health has been equally impressive and produced a healthier and better-educated working population. More women are joining the workforce while gender gaps in pay are gradually narrowing. Moving forward, the country aspires to reach the stage of a developed economy in the next two decades. Bangladesh needs to prepare its workforce for the emerging challenges for a dynamic economy in an increasingly globalized world. The economy is undergoing structural changes on several fronts. First, Bangladesh has transitioned from a largely traditional, agriculture-based economy to an industry and service-driven economy. Industry sector has been the main driving force for economic growth. Second, more recently, technological progress is rapidly changing the production and service modality. Firms need to not only constantly adjust their business and production modality with these technological changes but also have highly skilled manpower who can enable such change processes. Third, a growing and youthful workforce in Bangladesh provides a window of opportunity to improve productivity and accelerate economic growth. Equipping the young generation with the skills needed for jobs remains crucial. On one hand, employers are demanding higher-skilled professionals for technical and managerial positions to support the growing industry and service sectors. On the other hand, tertiary education institutes (TEIs) are struggling to produce employable graduates for the job market. Unemployment rates are consistently high among tertiary graduates, causing prolonged and frustrating joblessness for many. At the same time, the culture and practice of collaborative research to promote industry competitiveness and innovation has been largely missing in the country’s tertiary education landscape, undermining Bangladesh’s competitiveness ranking in the global knowledge economy. There is urgent need to identify and address the challenges in the sector and orient tertiary education toward the demands of the economy and labor market to help realize Bangladesh’s full economic development potential. On one hand, employers are demanding higher-skilled professionals for technical and managerial positions to support the growing industry and service sectors. On the other hand, tertiary education institutes (TEIs) are struggling to produce employable graduates for the job market. Unemployment rates are consistently high among tertiary graduates, causing prolonged and frustrating joblessness for many. At the same time, the culture and practice of collaborative research to promote industry competitiveness and innovation has been largely missing in the country’s tertiary education landscape, undermining Bangladesh’s competitiveness ranking in the global knowledge economy. There is urgent need to identify and address the challenges in the sector and orient tertiary education toward the demands of the economy and labor market to help realize Bangladesh’s full economic development potential.